Method for preparing formic acid through supercritical carbon dioxide electroreduction

By using a nanoflower-like Bi catalyst to perform CO2RR under supercritical carbon dioxide conditions, the problems of low current density and narrow electrochemical window are solved, and efficient preparation of formic acid is achieved.

CN119776852AActive Publication Date: 2025-04-08EAST CHINA UNIV OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510234750.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-08
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

The existing CO2RR technology has problems with low current density and narrow electrochemical windows, making it difficult to effectively utilize the fluctuations in renewable energy voltages.

Method used

The catalyst nanoflower-like Bi is used, and the electroreduction reaction is carried out under the supercritical state of carbon dioxide to increase the current density of the reaction and expand the electrochemical window.

Benefits of technology

The current density of CO2RR is significantly improved, and the electrochemical window is expanded, improving the efficiency and stability of the reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776852A_ABST
    Figure CN119776852A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing formic acid through supercritical carbon dioxide electroreduction, which comprises the following steps: under the condition that carbon dioxide is in a supercritical state, carrying out carbon dioxide electroreduction reaction to prepare formic acid; wherein the electrode loaded with the Bi with the nano flower-shaped morphology is used as a cathode; the pressure of the carbon dioxide electroreduction reaction is 7.5-9.5 Mpa, and the temperature is 35-55 DEG C. Compared with a traditional CO2RR, the problems that the current density is low and the electrochemical window is narrow are solved, and the technology with the high current density and the wide electrochemical window is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysis, and more specifically, relates to a method for preparing formic acid by electroreduction of supercritical carbon dioxide. Background Art

[0002] The burning of fossil fuels produces a large amount of carbon dioxide (CO2), which greatly increases the concentration of CO2 in the atmosphere, causing a large number of environmental problems. The CO2 electroreduction reaction (CO2RR) powered by clean energy such as wind and solar energy effectively reduces CO2 emissions.

[0003] Metallic Bi has high CO2RR activity and has unique advantages over other traditional metal catalysts due to its low price, low toxicity, environmental friendliness and high stability. However, metallic Bi catalysts in nanoparticle or two-dimensional nanosheet morphology have problems such as poor conductivity and limited exposure of active sites, which leads to low current density of CO2RR.

[0004] At the same time, in practical applications, since the voltage of renewable energy sources that provide CO2RR electricity fluctuates greatly and the voltage gap provided by different renewable energy sources is also large, a reaction system with a wider electrochemical window with high selectivity for formate / formic acid is required; however, the electrochemical window of CO2RR carried out at room temperature and pressure is narrow. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing formic acid by electroreduction of supercritical carbon dioxide. The method of the present invention improves the current density of the reaction and expands the electrochemical window by using a catalyst nanoflower-shaped Bi and performing electroreduction under the condition that carbon dioxide is in a supercritical state.

[0006] In order to achieve the above-mentioned object, the present invention provides a method for preparing formic acid by supercritical carbon dioxide electroreduction, the method comprising: preparing formic acid by electroreduction reaction of carbon dioxide under the condition that carbon dioxide is in a supercritical state; wherein an electrode loaded with Bi having a nanoflower-like morphology is used as a cathode; the pressure of the carbon dioxide electroreduction reaction is 7.5-9.5Mpa, and the temperature is 35-55°C.

[0007] The technical problem to be solved by the present invention is how to increase the current density of CO2RR and expand the electrochemical window. The present invention uses a catalyst nanoflower-shaped Bi and performs electroreduction under the condition that carbon dioxide is in a supercritical state (i.e., carbon dioxide is in a supercritical state under the conditions of a pressure of 7.5 to 9.5 MPa and a temperature of 35 to 55°C), thereby improving the conductivity of the catalyst, increasing the active sites, and also increasing the solubility of carbon dioxide in the solution and the diffusion capacity of carbon dioxide from the solution to the electrode surface, thereby increasing the current density of the reaction and expanding the electrochemical window.

[0008] In the present invention, the electrode loaded with nano-flower-like Bi is preferably carbon paper loaded with nano-flower-like Bi; further preferably, the preparation method of the electrode loaded with nano-flower-like Bi is to use BiOCl as a precursor and adopt an electrochemical in-situ reduction method to prepare the electrode loaded with nano-flower-like Bi. Wherein, the precursor BiOCl is synthesized by a solvothermal method: BiCl3 is dissolved in ethylene glycol, a surfactant sodium dodecylbenzene sulfonate is added, mixed evenly, and then deionized water is added and mixed evenly to obtain a mixed solution; then the mixed solution is subjected to a hydrothermal reaction, and the product is washed and dried to obtain a BiOCl precursor.

[0009] According to the present invention, preferably, in the method, the electrolyte used is a potassium bicarbonate aqueous solution, a mixed solution of an imidazole ionic liquid and water, or a mixed solution of an imidazole ionic liquid and methanol.

[0010] According to the present invention, preferably, the concentration of the potassium bicarbonate aqueous solution is 0.2-2.0 mol / L.

[0011] In the present invention, in the mixed solution of imidazole ionic liquid and water, the concentration of imidazole ionic liquid is preferably 5-30 mmol / L; in the mixed solution of imidazole ionic liquid and methanol, the concentration of imidazole ionic liquid is preferably 5-30 mmol / L.

[0012] According to the present invention, preferably, the imidazolium ionic liquid is at least one of 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim]PF6), 1-ethyl-3-methylimidazolium tetrafluoroborate ([Emim]BF4) and 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide ([Emim]NTF2).

[0013] According to the present invention, preferably, in the method, platinum is used as the anode; and Ag / AgCl electrode is used as the reference electrode.

[0014] According to the present invention, preferably, the reaction device is a diaphragm electrolyzer.

[0015] According to the present invention, preferably, the diaphragm of the diaphragm electrolyzer is a cation exchange membrane.

[0016] In the present invention, as a specific preferred embodiment, the method includes: carrying out a reaction in a diaphragm electrolyzer, adding electrolyte to the cathode chamber and the anode chamber of the diaphragm electrolyzer; using an electrode loaded with Bi having a nanoflower-like morphology as a cathode; using a Pt sheet as an anode; using an Ag / AgCl electrode as a reference electrode, which is arranged in the cathode chamber; introducing carbon dioxide into the cathode chamber and the anode chamber of the diaphragm electrolyzer, wherein the pressure in the cathode chamber and the anode chamber is 7.5 to 9.5 MPa, and the temperature is 35 to 55° C., applying a negative potential to the cathode for constant potential electrolysis, and thus producing formic acid.

[0017] The technical solution of the present invention has the following beneficial effects:

[0018] Compared with the traditional CO2RR, the present invention improves the problems of low current density and narrow electrochemical window, and provides a process with high current density and wide electrochemical window.

[0019] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.

[0021] Figure 1 An electron microscope scanning image of Bi on an electrode loaded with Bi having a nanoflower-like morphology used in accordance with an embodiment of the present invention is shown.

[0022] Figure 2 The electron microscope scanning image of Bi on the electrode loaded with Bi in nanoparticle morphology used in Comparative Example 1 of the present invention is shown. DETAILED DESCRIPTION

[0023] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0024] The present invention is further described below by examples:

[0025] In the following embodiments and comparative examples:

[0026] The Bi electrode loaded with nanoflower-like morphology was prepared by the following method:

[0027] (1) The synthesis of BiOCl precursor adopts solvothermal technology. The specific operation process is as follows: 0.12g BiCl3 is weighed and dissolved in 30mL ethylene glycol, and it is completely dissolved by ultrasonic treatment for 10 minutes. Then 0.1g sodium dodecylbenzene sulfonate (SDBS) is added to the solution, and ultrasonic treatment is continued for 10 minutes until it is evenly dispersed. Then 0.6mL deionized water is added and ultrasonic dispersion treatment is carried out for 10 minutes to mix it evenly. The mixed solution is transferred to a 100mL polytetrafluoroethylene-lined reactor and hydrothermally reacted at 200℃ for 4h. After the reaction is completed, the reactor is naturally cooled to room temperature. The solution after the reaction is filtered to obtain a white precipitate, which is washed three times with ethanol solvent. Finally, the washed precipitate is vacuum dried at 60℃ for 12h to obtain BiOCl precursor powder.

[0028] (2) Prepare an electrode loaded with nanoflower-like morphology of Bi by an electrochemical in-situ reduction process. The specific operation process is as follows: weigh 3 mg of BiOCl precursor and disperse it into a mixed solution consisting of 270 μL of ethanol and 30 μL of DuPont's Nafion solution with a mass concentration of 5%, ultrasonically treat for 20 minutes to obtain a uniform dispersion, take 100 μL of the dispersion and coat it on a 1 cm*1 cm hydrophobic carbon paper and dry it; in a standard three-electrode system, use the above carbon paper as the working electrode, the platinum mesh as the counter electrode, the Ag / AgCl electrode as the reference electrode, and the 0.5 M (mol / L) KHCO3 aqueous solution as the electrolyte, and reduce it at a constant potential of -0.9 V (vs. RHE) for 1 hour at room temperature and normal pressure to finally obtain an electrode loaded with nanoflower-like morphology of Bi (the morphology of the catalyst Bi is shown in FIG. 2 ). Figure 1 shown).

[0029] The diaphragm of the diaphragm electrolyzer used is Nafion 117 cation exchange membrane.

[0030] In the following examples and comparative examples: the ion chromatograph used for analysis was ICS-1100, Dionex Corporation, the mobile phase was 20 mM KOH aqueous solution, the flow rate was 1.0 mL / min (anion analysis column: IonPac AS15, guard column: AG15, suppressor: ADRS 600-4 mm, suppression current: 60 mA).

[0031] Example 1

[0032] 80mL of 0.5M KHCO3 aqueous solution was added to the cathode chamber and anode chamber of the diaphragm electrolyzer respectively; the electrode loaded with nanoflower-like Bi was used as the cathode; the Pt sheet was used as the anode; the Ag / AgCl electrode was used as the reference electrode and was set in the cathode chamber. The reaction temperature in the cathode chamber and the anode chamber was set to 35°C; CO2 was introduced into the cathode chamber and the anode chamber, and the pressure in the cathode chamber and the anode chamber of the electrolyzer was adjusted to 7.5MPa; when the temperature and pressure in the cathode chamber and the anode chamber reached the set value, constant potential electrolysis was performed under the conditions of electrode potential of -2.0, -2.5, -3.0, -3.5, and -4.0V (vs.Ag / AgCl), and the above negative potentials were applied to the cathode respectively. After the electrolysis was completed, the valves of the cathode chamber and the anode chamber were opened at the same time to release the residual pressure in the electrolytic cell. The liquid samples on the cathode side were collected and analyzed by ion chromatography. It was calculated that the formic acid Faradaic efficiency was higher than 70% at electrode potentials of -2.0, -2.5, -3.0, and -3.5 V (vs. Ag / AgCl), which were 71.67%, 76.92%, 91.72%, and 72.57%, respectively. The formic acid separation current density was 35.57 mA cm -2 、81.70mA cm -2 、178.98mA cm -2 、184.04mAcm -2 .

[0033] Example 2

[0034] 80mL of 0.5M KHCO3 aqueous solution was added to the cathode chamber and anode chamber of the diaphragm electrolyzer respectively; the electrode loaded with nanoflower-like Bi was used as the cathode; the Pt sheet was used as the anode; the Ag / AgCl electrode was used as the reference electrode and was set in the cathode chamber. The reaction temperature in the cathode chamber and the anode chamber was set to 35°C; CO2 was introduced into the cathode chamber and the anode chamber, and the pressure in the cathode chamber and the anode chamber of the electrolyzer was adjusted to 8.5MPa; when the temperature and pressure in the cathode chamber and the anode chamber reached the set value, constant potential electrolysis was performed under the conditions of electrode potentials of -2.0, -2.5, -3.0, -3.5, and -4.0V (vs.Ag / AgCl), and the above negative potentials were applied to the cathode respectively. After the electrolysis was completed, the valves of the cathode chamber and the anode chamber were opened simultaneously to release the residual pressure in the electrolytic cell. The liquid samples on the cathode side were collected and analyzed by ion chromatography. It was calculated that the formic acid Faradaic efficiency was higher than 70% at electrode potentials of -2.0, -2.5, -3.0, -3.5, and -4.0 V (vs. Ag / AgCl), which were 70.71%, 85.44%, 92.29%, 93.00%, and 70.86%, respectively. The formic acid separation current density was 43.84 mA cm -2 、81.50mA cm -2 、139.22mAcm-2 、212.28mA cm -2 、199.26mA cm -2 .

[0035] Example 3

[0036] 80mL of 0.5M KHCO3 aqueous solution was added to the cathode chamber and anode chamber of the diaphragm electrolyzer respectively; the electrode loaded with nanoflower-like Bi was used as the cathode; the Pt sheet was used as the anode; the Ag / AgCl electrode was used as the reference electrode and was set in the cathode chamber. The reaction temperature in the cathode chamber and the anode chamber was set to 35°C; CO2 was introduced into the cathode chamber and the anode chamber, and the pressure in the cathode chamber and the anode chamber of the electrolyzer was adjusted to 9.5MPa; when the temperature and pressure in the cathode chamber and the anode chamber reached the set value, constant potential electrolysis was performed under the conditions of electrode potentials of -2.0, -2.5, -3.0, -3.5, and -4.0V (vs.Ag / AgCl), and the above negative potentials were applied to the cathode respectively. After the electrolysis was completed, the valves of the cathode chamber and the anode chamber were opened simultaneously to release the residual pressure in the electrolytic cell. The liquid samples on the cathode side were collected and analyzed by ion chromatography. It was calculated that the Faraday efficiency of formic acid was higher than 70% at electrode potentials of -2.0, -2.5, and -3.0 V (vs. Ag / AgCl), which were 71.04%, 86.70%, and 79.05%, respectively. The current density of formic acid was 41.59 mA cm -2 、88.16mA cm -2 , 127.54mA cm -2 .

[0037] Example 4

[0038] 80mL of 0.5M KHCO3 aqueous solution was added to the cathode chamber and anode chamber of the diaphragm electrolyzer respectively; the electrode loaded with nanoflower-like Bi was used as the cathode; the Pt sheet was used as the anode; the Ag / AgCl electrode was used as the reference electrode and was set in the cathode chamber. The reaction temperature in the cathode chamber and the anode chamber was set to 45°C; CO2 was introduced into the cathode chamber and the anode chamber, and the pressure in the cathode chamber and the anode chamber of the electrolyzer was adjusted to 7.5MPa; when the temperature and pressure in the cathode chamber and the anode chamber reached the set value, constant potential electrolysis was performed under the conditions of electrode potentials of -2.0, -2.5, -3.0, -3.5, and -4.0V (vs.Ag / AgCl), and the above negative potentials were applied to the cathode respectively. After the electrolysis was completed, the valves of the cathode chamber and the anode chamber were opened simultaneously to release the residual pressure in the electrolytic cell. The liquid samples on the cathode side were collected and analyzed by ion chromatography. It was calculated that the formic acid Faradaic efficiency was higher than 70% at electrode potentials of -2.5, -3.0, and -3.5 V (vs. Ag / AgCl), which were 75.25%, 90.29%, and 74.85%, respectively. The formic acid separation current density was 93.97 mA cm -2 、188.77mA cm -2 、219.09mA cm -2 .

[0039] Example 5

[0040] 80mL of 0.5M KHCO3 aqueous solution was added to the cathode chamber and anode chamber of the diaphragm electrolyzer respectively; the electrode loaded with nanoflower-like Bi was used as the cathode; the Pt sheet was used as the anode; the Ag / AgCl electrode was used as the reference electrode and was set in the cathode chamber. The reaction temperature in the cathode chamber and the anode chamber was set to 55°C; CO2 was introduced into the cathode chamber and the anode chamber, and the pressure in the cathode chamber and the anode chamber of the electrolyzer was adjusted to 7.5MPa; when the temperature and pressure in the cathode chamber and the anode chamber reached the set value, constant potential electrolysis was performed under the conditions of electrode potentials of -2.0, -2.5, -3.0, -3.5, and -4.0V (vs.Ag / AgCl), and the above negative potentials were applied to the cathode respectively. After the electrolysis was completed, the valves of the cathode chamber and the anode chamber were opened simultaneously to release the residual pressure in the electrolytic cell. The liquid samples on the cathode side were collected and analyzed by ion chromatography. It was calculated that when the electrode potential was -2.5 and -3.0 V (vs. Ag / AgCl), the formic acid Faradaic efficiency was higher than 70%, 77.95% and 73.62% respectively, and the formic acid separation current density was 111.67 mA cm -2 、164.98mA cm -2 .

[0041] Example 6

[0042] 80mL of 0.2M KHCO3 aqueous solution was added to the cathode chamber and anode chamber of the diaphragm electrolyzer respectively; the electrode loaded with nanoflower-like Bi was used as the cathode; the Pt sheet was used as the anode; the Ag / AgCl electrode was used as the reference electrode and was set in the cathode chamber. The reaction temperature in the cathode chamber and the anode chamber was set to 35°C; CO2 was introduced into the cathode chamber and the anode chamber, and the pressure in the cathode chamber and the anode chamber of the electrolyzer was adjusted to 7.5MPa; when the temperature and pressure in the cathode chamber and the anode chamber reached the set value, constant potential electrolysis was performed under the conditions of electrode potential of -2.0, -2.5, -3.0, -3.5, and -4.0V (vs.Ag / AgCl), and the above negative potentials were applied to the cathode respectively. After the electrolysis was completed, the valves of the cathode chamber and the anode chamber were opened at the same time to release the residual pressure in the electrolytic cell. The liquid samples on the cathode side were collected and analyzed by ion chromatography. It was calculated that the formic acid Faraday efficiency was higher than 70% at the electrode potential of -2.5 and -3.0 V (vs. Ag / AgCl), which were 75.34% and 78.83% respectively. The formic acid separation current density was 30.26 mA cm -2 、74.23mA cm -2 .

[0043] Example 7

[0044] 80mL of 0.3M KHCO3 aqueous solution was added to the cathode chamber and anode chamber of the diaphragm electrolyzer respectively; the electrode loaded with nanoflower-like Bi was used as the cathode; the Pt sheet was used as the anode; the Ag / AgCl electrode was used as the reference electrode and was set in the cathode chamber. The reaction temperature in the cathode chamber and the anode chamber was set to 35°C; CO2 was introduced into the cathode chamber and the anode chamber, and the pressure in the cathode chamber and the anode chamber of the electrolyzer was adjusted to 7.5MPa; when the temperature and pressure in the cathode chamber and the anode chamber reached the set value, constant potential electrolysis was performed under the conditions of electrode potential of -2.0, -2.5, -3.0, -3.5, and -4.0V (vs.Ag / AgCl), and the above negative potentials were applied to the cathode respectively. After the electrolysis was completed, the valves of the cathode chamber and the anode chamber were opened at the same time to release the residual pressure in the electrolytic cell. The liquid samples on the cathode side were collected and analyzed by ion chromatography. It was calculated that the formic acid Faraday efficiency was higher than 70% at electrode potentials of -2.5, -3.0, and -3.5 V (vs. Ag / AgCl), which were 73.77%, 85.36%, and 75.99%, respectively. The formic acid separation current density was 43.89 mA cm -2 , 109.91mA cm -2 、127.06mA cm -2 .

[0045] Example 8

[0046] 80mL of 0.4M KHCO3 aqueous solution was added to the cathode chamber and anode chamber of the diaphragm electrolyzer respectively; the electrode loaded with nanoflower-like Bi was used as the cathode; the Pt sheet was used as the anode; the Ag / AgCl electrode was used as the reference electrode and was set in the cathode chamber. The reaction temperature in the cathode chamber and the anode chamber was set to 35°C; CO2 was introduced into the cathode chamber and the anode chamber, and the pressure in the cathode chamber and the anode chamber of the electrolyzer was adjusted to 7.5MPa; when the temperature and pressure in the cathode chamber and the anode chamber reached the set value, constant potential electrolysis was performed under the conditions of electrode potential of -2.0, -2.5, -3.0, -3.5, and -4.0V (vs.Ag / AgCl), and the above negative potentials were applied to the cathode respectively. After the electrolysis was completed, the valves of the cathode chamber and the anode chamber were opened at the same time to release the residual pressure in the electrolytic cell. The liquid samples on the cathode side were collected and analyzed by ion chromatography. It was calculated that the Faraday efficiency of formic acid was higher than 70% at electrode potentials of -2.5, -3.0, and -3.5 V (vs. Ag / AgCl), which were 76.43%, 87.22%, and 78.93%, respectively. The current density of formic acid was 58.29 mA cm -2 、119.16mA cm -2 、140.54mA cm -2 .

[0047] Comparative Example 1

[0048] 80 mL of 0.5 M KHCO3 aqueous solution was added to the cathode chamber and the anode chamber of the diaphragm electrolyzer respectively; the electrode loaded with nanoparticle-shaped Bi was used as the cathode. The electrode loaded with nanoparticle-shaped Bi was purchased from Shanghai Myrel Biochemical Technology Co., Ltd. with the item number B802618. The morphology of the catalyst Bi is as shown in Figure 2 As shown; Pt sheet is used as anode; Ag / AgCl electrode is used as reference electrode and is set in cathode chamber. Set the reaction temperature of cathode chamber and anode chamber to 35℃; introduce CO2 into cathode chamber and anode chamber, and adjust the pressure of cathode chamber and anode chamber of electrolytic cell to 7.5MPa; wait for the temperature and pressure of cathode chamber and anode chamber to reach the set value, and carry out constant potential electrolysis under the conditions of electrode potential of -2.0, -2.5, -3.0, -3.5, -4.0V (vs.Ag / AgCl), respectively, and the above negative potentials are applied to cathode respectively. After the electrolysis is completed, open the valves of cathode chamber and anode chamber at the same time to release the residual pressure in electrolytic cell, collect liquid samples on cathode side and carry out ion chromatography analysis. It is calculated that when the electrode potential is -2.5 and -3.0V (vs.Ag / AgCl), the formic acid Faraday efficiency is higher than 70%, which are 70.95% and 72.68% respectively, and the formic acid separation current density is 61.32mA cm -2 、89.93mA cm -2 .

[0049] Comparative Example 2

[0050] 80mL of 0.5M KHCO3 aqueous solution was added to the cathode chamber and anode chamber of the diaphragm electrolyzer respectively; the electrode loaded with nanoflower-like Bi was used as the cathode; the Pt sheet was used as the anode; the Ag / AgCl electrode was used as the reference electrode and was set in the cathode chamber. The reaction temperature in the cathode chamber and the anode chamber was set to 35°C; CO2 was introduced into the cathode chamber and the anode chamber, and the pressure in the cathode chamber and the anode chamber of the electrolyzer was adjusted to normal pressure; when the temperature and pressure in the cathode chamber and the anode chamber reached the set value, constant potential electrolysis was performed under the conditions of electrode potential of -1.4, -1.5, -1.6, -1.7, -1.8, and -2.0V (vs.Ag / AgCl), and the above negative potentials were applied to the cathode respectively. After the electrolysis, the cathode liquid samples were collected and analyzed by ion chromatography. It was calculated that the formic acid Faraday efficiency was higher than 70% at the electrode potential of -1.5 and -1.6 V (vs. Ag / AgCl), which were 76.82% and 70.11% respectively. The formic acid separation current density was 13.82 mA cm -2 , 22.23mAcm -2 , while when the electrode potential is -2.0 V (vs. Ag / AgCl), no formic acid is generated.

[0051] Comparative Example 3

[0052] 80mL of 0.5M KHCO3 aqueous solution was added to the cathode chamber and anode chamber of the diaphragm electrolyzer respectively; the electrode loaded with nanoflower-like Bi was used as the cathode; the Pt sheet was used as the anode; the Ag / AgCl electrode was used as the reference electrode and was set in the cathode chamber. The reaction temperature in the cathode chamber and the anode chamber was set to 65°C; CO2 was introduced into the cathode chamber and the anode chamber, and the pressure in the cathode chamber and the anode chamber of the electrolyzer was adjusted to 7.5MPa; when the temperature and pressure in the cathode chamber and the anode chamber reached the set value, constant potential electrolysis was performed under the conditions of electrode potentials of -2.0, -2.5, -3.0, -3.5, and -4.0V (vs.Ag / AgCl), and the above negative potentials were applied to the cathode respectively. After the electrolysis was completed, the valves of the cathode chamber and the anode chamber were opened simultaneously to release the residual pressure in the electrolytic cell. The liquid samples on the cathode side were collected and analyzed by ion chromatography. It was calculated that the formic acid Faraday efficiency was less than 70% at the above electrode potentials. When the electrode potential was -2.5 V (vs. Ag / AgCl), the formic acid Faraday efficiency was the highest, which was 48.01%. The formic acid separation current density was 51.56 mA cm -2 .

[0053] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A method for preparing formic acid by electroreduction of supercritical carbon dioxide, characterized in that: The method comprises: preparing formic acid by electro-reduction reaction of carbon dioxide under the condition that carbon dioxide is in a supercritical state; wherein an electrode loaded with Bi in nano-flower-like morphology is used as a cathode; and the pressure of the carbon dioxide electro-reduction reaction is 7.5-9.5Mpa and the temperature is 35-55°C.

2. The method according to claim 1, wherein: In the method, the electrolyte used is a potassium bicarbonate aqueous solution, a mixed solution of an imidazole ionic liquid and water, or a mixed solution of an imidazole ionic liquid and methanol.

3. The method according to claim 2, wherein: The concentration of the potassium bicarbonate aqueous solution is 0.2-2.0 mol / L.

4. The method according to claim 2, wherein: The imidazole ionic liquid is at least one of 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium tetrafluoroborate and 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide.

5. The method according to claim 1, wherein: In the method, platinum is used as the anode and Ag / AgCl electrode is used as the reference electrode.

6. The method according to claim 1, wherein: The reaction device is a diaphragm electrolyzer.

7. The method according to claim 6, wherein: The diaphragm of the diaphragm electrolyzer is a cation exchange membrane.

Citation Information

Patent Citations

  • Method for preparing bismuthyl chloride nano-flower

    CN101844808A

  • Process and high surface area electrodes for the electrochemical reduction of carbon dioxide

    CN104619886A

  • Copper-bismuth aerogel, electrode and preparation method and application of copper-bismuth aerogel

    CN115090894A

  • Formic Acid Synthesis by Electrochemical Reduction ofCarbon Dioxide

    KR1020040009875A

  • Conversion of liquid co2

    US20240352596A1